Maternal satisfaction with the quality of post-abortion care in Ethiopia at teaching hospitals of Amhara regional state by 2023 - Besfat Berihun Erega; Wassie Yazie Ferede; Assefa Kebie Mitiku; Rahel Birhanu Arage; Enyew Dagnew Yehuala; Begizew Yimenu Mekuriaw; Temesgen Dessie Mengistu; Tigist Seid Yimer; Eyob Shitie Lake (BMC Pregnancy and Childbirth)
Abstract Background Every year, complications from abortion cause millions of women’s serious injuries and over 47,000 deaths globally. While many regions of Sub-Saharan Africa restrict access to safe abortion procedures, Ethiopia’s government is attempting to address maternal morbidity and mortality associated with abortion by offering post-abortion care services to all women. The primary determinant of the quality of health treatment is thought to be client satisfaction. Services for post-abortion are still lacking and disregarded in Ethiopia’s contemporary healthcare system. Thus, this study’s main goal was to investigate the state of post-abortion care services, with a particular emphasis on client satisfaction, the suitability of legal requirements for safe abortion services, service provider competency, and the establishment of animosity. Methods A facility-based cross sectional study was conducted from March 01/2023 to July 30/2023. The study was conducted at eight selected maternity teaching hospitals located in the Amhara regional state. Eight BSc midwives who had received three days of training collected the data via a structured questionnaire. A quota sampling technique was carried out for all post-abortion patients who were consecutively served at facilities. The chi-square test and multivariable logistic regression methods were employed using SPSS 23. The strength of associations and significance level were examined using P values of less than 0.05 and odds ratios at 95% confidence intervals respectively. Multicollinearity and model fitness were also checked. Results A total sample size of 384 were employed with a response rate of 100%.The overall magnitude of women’s satisfaction in this study was (34.11% (27.45%_39.05%)). Educational status, living solely, having an unplanned pregnancy and having a hostile infrastructure are the determining factors for women’s satisfaction with the quality of Post-abortion care. Conclusion and recommendation The overall magnitude of women’s satisfaction (34.11% (27.45%_39.05%)) is extremely low in this study. Therefore, health care providers and policy makers in the health sector had to struggle with the quality of PAC for improved client satisfaction.